The influence of aspect markers and tense on the action-sentence compatibility effect in Mandarin action sentence comprehension - Ning Fan; Hongkai Zhu; Zhiwei Cai (PLoS ONE, 2026)
The Action-sentence Compatibility Effect (ACE) suggests that action sentences comprehension is based on embodied mental simulation. In studies of English, aspect markers and tense has been shown to influence ACE; however, their effects remain unclear in Mandarin. This study utilized Mandarin action sentences with single objects and employed the classic sentence sensibility judgment paradigm to investigate the ACE for concrete and abstract action sentences under different aspect marker (Experiment 1 and 2) or future tense (Experiment 3) conditions across three experiments. The results showed that ACE occurred for both concrete and abstract action sentences in the progressive aspect, perfective aspect, and future tense. Action simulation during sentence comprehension was unaffected by the type of aspect markers and future tense or the concreteness/abstractness of the sentences. These findings suggest that the comprehension of Mandarin action sentences relies on the mental simulation of verbs. Moreover, aspect markers and future tense in Mandarin do not influence the mental simulation process, and Mandarin action sentences comprehension may be centered around the mental simulation of the verb.